Molar incisor hypomineralization: prevalence, severity and clinical consequences in Brazilian children - Costa-Silva, Cristiane Maria da [UNESP]; Jeremias, Fabiano [UNESP]; Souza, Juliana Feltrin de [UNESP]; Loiola Cordeiro, Rita de Cassia [UNESP]; Santos-Pinto, Lourdes Aparecida Martins dos [UNESP]; Cilense Zuanon, Angela Cristina [UNESP] (Wiley-Blackwell, 2010)
Background.The prevalence of molar incisor hypomineralization (MIH) varies considerably around the world; however, few studies have examined MIH in South American countries.Objective.To evaluate the prevalence, severity, and clinical consequences of MIH in Brazilian children residing in rural and urban areas of the municipality of Botelhos, Minas Gerais, Brazil.Methods.Children aged 6 to 12 years (n = 918) with all four-first permanent molars erupted had these teeth evaluated according to the European Academy of Paediatric Dentistry (EAPD) criteria. The examinations were conducted by two previously trained examiners, and the dental impact caused by MIH was evaluated with the Decayed, Missing and Filled Teeth (DMFT) index (WHO).Results.Molar incisor hypomineralization was present in 19.8% of the 918 children, with a higher prevalence in rural areas. The majority of the defects presented were demarcated opacities without post-eruptive structural loss, which has been considered as mild defects. Children with MIH had higher DMFT values.Conclusion.Despite the high prevalence of MIH, the severity of the defects was mild. The results indicate a positive association between MIH and the presence of dental caries.